Built-In Content sebagai Pesan Komunikasi Pemasaran pada Program Rating 5 GTV - Amanu, Zhevio Aufa; Priatna, Wahyu Budi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
This study analyzes the effectiveness of built-in content strategies as a form of marketing communication in the "Rating 5" program on GTV. A descriptive qualitative approach is employed to explore audience perceptions and evaluate how effectively this strategy creates an emotional connection between the brand and viewers. Data were collected through in-depth interviews with key informants and analyzed using the Integrated Marketing Communication (IMC) framework. The findings reveal that the success of built-in content strategies is influenced by contextual relevance and seamless integration within the program’s narrative, which enhances positive brand perception without disrupting the viewing experience. This strategy also plays a role in strengthening consumer-brand relationships amid digital media disruption.